Co-creation in cultural industries: Developing art toys for youth tourism through theoretical integration - Kittichai Kasemsarn; Farnaz Nickpour (Journal of Open Innovation Technology Market and Complexity, 2026)
This research addresses two key challenges in cultural tourism. First, youths aged 18–25 show limited interest in cultural tourism due to outdated presentation methods and cultural products. Second, there is insufficient understanding of how to create culturally authentic products for youths while maintaining sustainable business models. The study aims to understand youth tourist preferences and develop a co-creation framework for designing art toys that promote cultural tourism. A mixed-methods approach was used, combining questionnaires completed by 400 youths in Bangkok with co-design workshops involving 11 professionals from marketing and design teams. The findings show that 31% of the youths prioritized the cuteness of art toys. Participants expressed a preference for art toys that reflect Thai identity without an old-fashioned style (Mean = 3.81/5) and reported high interest in cultural tourism (Mean = 4.01/5). Workshop outcomes emphasized simplifying patterns, using nostalgia marketing, and creating location-exclusive cultural art toys. The study proposes the Youth-Centered Art Toy Framework for Cultural Tourism, which demonstrates how co-creation can transform cultural industries through stakeholder collaboration. The framework contributes to existing knowledge by providing empirical data to support cultural preservation within business model development and by demonstrating how the integration of four theories can generate sustainable revenue streams.
Keywords: Diverse Aspects of Tourism Research; Nostalgia and Consumer Behavior; Service and Product Innovation